Differential halothane binding and effects on serum albumin and myoglobin. - Eckenhoff, R G (1998)
To understand further the weak molecular interactions between inhaled anesthetics and proteins, we studied the character and dynamic consequences of halothane binding to bovine serum albumin (BSA) and myoglobin using photoaffinity labeling and hydrogen-tritium exchange (HX). We find that halothane binds saturably and with submillimolar affinity to BSA, but either nonspecifically or with considerably lower affinity to myoglobin. Titration of halothane binding with guanidine hydrochloride suggested more protection of binding sites from solvent in BSA as compared with myoglobin. Protection factors for slowly exchanging albumin hydrogens are increased in a concentration-dependent manner by up to 27-fold with 10 mM halothane, whereas more rapidly exchanging groups of albumin hydrogens have either unaltered or decreased protection factors. Protection factors for slowly exchanging hydrogens in myoglobin are decreased by halothane, suggesting destabilization through binding to an intermediate or completely unfolded conformer. These results demonstrate the conformation dependence of halothane binding and clear dynamic consequences that correlate with the character of binding in these model proteins. Preferential binding and stabilization of different conformational states may underlie anesthetic-induced protein dysfunction, as well as provide an explanation for heterogeneity of action.